PTU-070 Non-adherence With Rectal Preparations In Colitic Patients. Fact Or Fiction?. (9th June 2014) - Kok, B; Waters, A; Jenkins, A
Abstract : Introduction: Rectal preparations containing steroids or 5-aminosalicylates are an effective treatment for distal colitis. Nonetheless, it is perceived that this therapy is associated with poor levels of adherence and that patients are not readily accepting of it. This might make gastroenterologists reluctant to prescribe rectal preparations. The patient experience and factors determining adherence with this modality of treatment have not been investigated before. The aim of our survey is to evaluate patient compliance with rectal preparations and explore the possible reasons why compliance is not always achieved. Methods: A short anonymised survey was distributed over a 3-month period at general gastroenterology and IBD outpatient clinics to patients with a known diagnosis of ulcerative colitis. There were questions on baseline demographics and other details relating to compliance. A free text option was also available for suggestions that could improve compliance. Results: Over the period November 2013–January 2014, a total of 59 completed surveys were received. 21 of 59 patients (36%) had never been prescribed a rectal preparation. Of the remaining 38 patients with reported experience of rectal preparations, 60% were male with a median age of 45 years. Surprisingly, 76% of these (29 patients) answered 'Yes' to being compliant with the preparation (s), and they had been prescribed courses ranging from once/day for 2 weeks to thrice/day long-term. 20 patients had been prescribed foam and/or liquid enemas, 8 patients a suppository, and 1 patient a suppository and foam enema. 93% of the compliant patients reported an improvement in their symptoms with the use of rectal preparations. Though compliant, 24% reported 'Yes' to having difficulties using the rectal preparation citing "insertion difficulties" and "difficulty retaining the fluid" and "at work" as the main reasons. When asked for suggestions to improve compliance, 62% felt reduction of treatment frequency to once/day would help, and 21% felt that better explanation about administration would help. Of the 9 patients who admitted to being noncompliant, 3 had difficulties with administration, 2 experienced pain, and the majority felt that a better explanation about administration would have improved compliance. As expected, the majority of noncompliant patients felt that the rectal preparation had made no difference to their symptoms. Conclusion: Compliance with prescribed rectal preparations is surprisingly high. This is an encouragement to continue promoting its use. Compliance could be further improved by allowing for patient factors such as work hours and adjusting dosing times, and by dedicating time to explain how the medication should be administered. Disclosure of Interest: None Declared.